From VICTORIA to VICTOR: Where Vericiguat Fits in HFrEF Care - Skibicka, Katarzyna; Wesołowska, Weronika; Jaśniak, Albert; Bujak, Robert (Journal of Education, Health and Sport, 2025)
Background. Vericiguat, an oral soluble guanylate cyclase stimulator, augments impaired NO-sGC-cGMP signaling in heart failure with reduced ejection fraction (HFrEF). The pivotal VICTORIA trial enrolled high-risk patients with recent worsening heart failure (WHF) and showed a reduction in the composite of cardiovascular (CV) death or first HF hospitalization, whereas the subsequent VICTOR trial tested ambulatory, clinically stable HFrEF without recent WHF and did not meet its primary endpoint. Objective. To synthesize contemporary evidence on vericiguat after VICTORIA and VICTOR, clarify patient selection and optimal timing and position the drug within guideline-directed medical therapy. Results. In VICTORIA (n≈5,050), vericiguat reduced the primary composite of CV death or first HF hospitalization versus placebo on top of contemporary therapy with acceptable safety and small increases in hypotension and anemia. VICTOR (n≈6,100) did not meet its primary composite in stable ambulatory HFrEF without recent WHF, secondary analyses signaled lower CV and all-cause mortality. A pooled patient-level analysis across VICTORIA+VICTOR (≈11,000 patients) suggested a significant reduction in the composite outcome across a broader risk spectrum. Guidelines continue to recommend vericiguat primarily after recent WHF despite optimized foundational therapy. Conclusion. Vericiguat remains most compelling for high-risk HFrEF after recent worsening, in stable ambulatory patients, evidence indicates a possible mortality signal but the overall effect on the composite outcome is uncertain and may depend on baseline risk. Careful selection (recent WHF, SBP ≥100 mmHg, on quadruple therapy), dose uptitration with food, and attention to anemia, hypotension, pregnancy risk, and PDE-5 interactions optimize real-world value.